2022
DOI: 10.1038/s41564-022-01096-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal gut virome analysis identifies specific viral signatures that precede necrotizing enterocolitis onset in preterm infants

Abstract: Necrotizing enterocolitis (NEC) is a serious consequence of preterm birth and is often associated with gut bacterial microbiome alterations. However, little is known about the development of the gut virome in preterm infants, or its role in NEC. Here, using metagenomic sequencing, we characterized the DNA gut virome of 9 preterm infants who developed NEC and 14 gestational age-matched preterm infants who did not. Infants were sampled longitudinally before NEC onset over the first 11 weeks of life. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 55 publications
4
42
0
Order By: Relevance
“…In another recent study, stool samples obtained from 9 infants with NEC infants and 14 controls matched for weight and gestational age, showed reduced viral beta diversity over the 10 days before NEC onset. This study also identified that viral NEC-associated contigs belonging to Myoviridae , Podoviridae and Siphoviridae are associated with the time period 0–10 d post NEC onset ( 137 ).…”
Section: Intestinal Microbiome and Necmentioning
confidence: 85%
“…In another recent study, stool samples obtained from 9 infants with NEC infants and 14 controls matched for weight and gestational age, showed reduced viral beta diversity over the 10 days before NEC onset. This study also identified that viral NEC-associated contigs belonging to Myoviridae , Podoviridae and Siphoviridae are associated with the time period 0–10 d post NEC onset ( 137 ).…”
Section: Intestinal Microbiome and Necmentioning
confidence: 85%
“…For instance, VirSorter searches the database of expected proteins up front using probabilistic similarity and reference homology to identify viral signals, but the disadvantage is that it does not fully distinguish between virus and nonvirus Pfam annotations ( Roux et al, 2015 ). Kaelin et al (2022) employed VirSorter v.1.0.5 to identify circular contigs of candidate viruses. Another tool, Meta-genomic Analysis and Retrieval of Viral Elements (MARVEL), which aggregates annotation and sequence signature information of previously identified phages, was developed to identify and predict double-stranded DNA phage sequences in macrogenomic boxes.…”
Section: Classification and Predictionmentioning
confidence: 99%
“…Understanding the development and maturation of the infant virome may uncover alterations that predict disease. In a study of necrotizing enterocolitis (NEC), a condition consisting of inflammation in intestinal tissue in preterm infants, Kaelin et al [33 ] studied the virome in preterm infants and its association with NEC. This condition is thought to be associated with gut bacterial alterations [34,35].…”
Section: The Infant Gut Virome -Necrotizing Enterocolitismentioning
confidence: 99%
“…This condition is thought to be associated with gut bacterial alterations [34,35]. Metagenomic sequencing of the gut virome of nine preterm infants who developed NEC and 14 gestational age-matched preterm infants were characterized [33 ▪ ]. Longitudinal sampling before NEC onset was conducted over the first eleven weeks of life.…”
Section: The Infant Gut Virome – Necrotizing Enterocolitismentioning
confidence: 99%